Rickettsial pathogens drive microbiota assembly in Hyalomma marginatum and Rhipicephalus bursa ticks - Maitre, Apolline; Wu‐Chuang, Alejandra; Mateos‐Hernández, Lourdes; Piloto‐Sardiñas, Elianne; Foucault‐Simonin, Angélique; Cicculli, Vincent; Moutailler, Sara; Paoli, Jean‐Christophe; Falchi, Alessandra; Obregón, Dasiel; Cabezas‐Cruz, Alejandro (Molecular ecology, 2023)
Most tick‐borne pathogens (TBPs) are secondarily acquired by ticks during feeding on infected hosts, which imposes ‘priority effect’ constraints, as arrival order influences the establishment of new species in a microbial community. Here we tested whether once acquired, TBPs contribute to bacterial microbiota functioning by increasing community stability. For this, we used Hyalomma marginatum and Rhipicephalus bursa ticks collected from cattle in different locations of Corsica and combined 16S rRNA amplicon sequencing and co‐occurrence network analysis, with high‐throughput pathogen detection, and in silico removal of nodes to test for impact of rickettsial pathogens on network properties. Despite its low centrality, Rickettsia showed preferential connections in the networks, notably with a keystone taxon in H. marginatum, suggesting facilitation of Rickettsia colonisation by the keystone taxon. In addition, conserved patterns of community assembly in both tick species were affected by Rickettsia removal, suggesting that privileged connections of Rickettsia in the networks make this taxon a driver of community assembly. However, Rickettsia removal had minor impact on the conserved ‘core bacterial microbiota’ of H. marginatum and R. bursa. Interestingly, networks of the two tick species with Rickettsia have similar node centrality distribution, a property that is lost after Rickettsia removal, suggesting that this taxon drives specific hierarchical interactions between bacterial microbes in the microbiota. The study indicates that tick‐borne Rickettsia play a significant role in the tick bacterial microbiota, despite their low centrality. These bacteria are influential and contribute to the conservation of the ‘core bacterial microbiota’ while also promoting community stability.